Wrocław public transport passengers’ satisfaction survey by means of CSI and IPA - Dziaduch, Izabela (Economics and Environment, 2023)
The purpose of this paper was to assess the level of satisfaction of passengers using public transport services in Wrocław and to identify the quality characteristics that the service provider needs to improve if it wants to increase the overall quality of its services. The passenger satisfaction survey was conducted according to the stages of the developed procedure outlined in the article. In pursuit of the stated goal, CSI and IPA were used. The main measurement tool used was a survey questionnaire. The survey was conducted on a sample of 500 respondents, which allows us to trust the results at 95%, assuming an “estimation error” of ± 5%. A total of 14 transport demands were selected to evaluate the level of satisfaction of passengers using services provided by MPK Wrocław. Statistical analysis of the data was carried out using Statistica 13.3 software and using functions and commands available in Microsoft Excel. The results obtained allowed us to conduct a detailed analysis related to the level of the services quality of the Wrocław’s public transport. These results should be used by urban transport organisers and operators to shape their transport offerings, primarily in terms of increasing the quality of transport services. This is very important since it is, among other things, the quality of public mass transport that determines the quality of life of residents, as well as the conditions for economic development of the transport network.